PENGEMBANGAN MODUL MULTIREPRESENTASI BERBASIS HIGH ORDER THINKING SKILLS (HOTS) PADA MATERI GERAK LURUS - Ridno Afrianto; Nur Islami; Azizahwati Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study aims to produce a multi-representation module based on High Order Thinking Skills (HOT) that is valid on straight motion material and can be used in learning. The type of research that will be used is research and development (according to Sugiyono). The object of this research is a multi-representation module based on High Order Thingking Skills (HOTS) on straight motion material. The research instrument used was a validation sheet for developing High Order Thinking Skills (HOTS) multirepresentation modules that would be prepared based on standard assessment indicators set by the Ministry of National Education regarding the guidelines for writing modules with some modifications according to the requiredmodule specifications. The steps that will be taken to conduct data analysis in this study are to convert the module validation sheet using a Likert scale in order to obtain quantitative data . The results obtained showed that the aspects of the feasibility of the content, language, graphics and presentation of each module are valid with good and very good categories. Thus it can be concluded that the multi-representation module based on High Order Thinking Skills (HOTS) on straight motion material has been valid based on aspects of content worthiness, language, graphics and presentation so that it is appropriate to be used as a learning resource that guides students in understanding straight motion material.Key Words:Multi-Representation Module, High Order Thinking Skills (HOTS), Straight Motion.